Eiro ieviešana ne eiro zonas valstīs - Abazi, Venera (Latvijas Universitāte, 2012)
Within the framework of the master thesis „Implementation of Euro in non-euro zone countries” the author analysis the importance of the Euro as a national currency and it’s benefits in the countries which are not in euro area. Author investigates the effects of the Euro in economy and looks at the challenges that Kosovo (case study) faced after the conflict of 1999 for choosing the monetary structure, by introducing Deutsche Mark and toward to the Euro. The results of the research show that despite some indicators that might be affected from global economic crisis, the costs consider acceptable compared to the advantages that were brought to the Kosovo economy by the introduction of Euro. The master thesis consists of 104 pages in total, there are 9 appendixes and includes 10 tables and 33images. Key phrases: Euro, benefits, eurozone, monetary policy, banking system, impacts of financial economic crisis.
Implementation of euro in non-euro zone countries
Keywords: Vadībzinātne